Multi-resolution wavelet pitch controller for spar-type floating offshore wind turbines including wave-current interactions - Fitzgerald, Breiffni; Basu, Biswajit (My University, 2020)
This paper proposes a wavelet multi-resolution based individual pitch control strategy for spar-type floating offshore wind turbines (FOWTs) and investigates its performance under joint wind-wave-current loads considering the effects of wave-current interactions. A multi-resolution analysis (MRA) based wavelet controller that modifies an optimal control problem cast in linear quadratic regulator (LQR) form constrained to a band of frequency has been used in this paper. The weighting matrices of the LQ regulator are varied in different frequency bands depending on the emphasis to be placed on the response energy and control effort to minimize the cost functional of that frequency band. This formulation results in frequency band dependent controller gains that lead to a time-varying controller. Daubechies wavelet is used in the MRA based filter that ensures perfect decomposition of the time signal over a finite interval and fast numerical implementation for control application. The multi-resolution wavelet-LQR individual blade pitch controller is used to control blade out-of-plane vibrations with additional emphasis on 1P frequency of the wind turbine. The emphasis on 1P frequency along with the blade's out-of-plane natural frequency is shown to reduce aerodynamic loads corresponding to 1st rotational frequency of the wind turbine which in turn reduces vibrations in other modes of the wind turbine. The proposed controller is simulated using a 5-MW baseline offshore wind turbine with realistic operational conditions including wave-current interactions. The controller has been proved to be effective in every analyzed met-ocean condition.
PUBLISHED
Keywords: Multi-resolution wavelet LQR; Individual pitch control; Wave-current interaction; Spar-type floating offshore wind turbine; Smart & Sustainable Planet; ENERGY; Renewable Energy Sources; Renewable energy; Structural Engineering; WIND; Wind Energy and Wind Turbines; Wind Energy, General; Wind power; Wind, Wind Energy Engineering